Effects of access to pasture on performance, carcass composition, and meat quality in broilers: a meta-analysis - Sales, J (Poultry science, 2014)
Consumer preference for poultry meat from free-range birds is not justified by scientific evidence. Inconsistency in results among studies on the effects of access to pasture on performance, carcass composition, and meat quality has led to a meta-analysis to quantify effects. After identification of studies where response variables were directly compared between birds with and without access to pasture, standardized effect sizes were used to calculate differences. The effect size for growth combined according to a fixed effect model did not present heterogeneity (P = 0.116). However, with feed intake and feed efficiency, variability among studies (heterogeneity with P-values of below 0.10) was influenced by more than sampling error. Carcass yield was the only carcass component that showed heterogeneity (P = 0.008), whereas numerous response variables related to meat quality were not homogenous. The use of subgroup analysis and meta-regression to evaluate the sources of heterogeneity was limited by ill-defined explanatory variables and few values available within response variables. Consequently, between-study variability was accounted for by use of random effects models to combine effect sizes. According to these, few response variables were influenced by pasture access. Fat concentrations in breast (mean effect size = -0.500; 95% CI = -0.825 to -0.175; 11 studies; 14 comparisons), thigh (mean effect size = -0.908; 95% CI = -1.710 to -0.105; 4 studies; 5 comparisons) and drum (mean effect size = -1.223; 95% CI = -2.210 to -0.237; 3 studies; 3 comparisons) muscles were decreased in free-range birds. Access to pasture increased (P < 0.05) or tended to increase (P < 0.10) protein concentrations in the respective commercial cuts. It is concluded that factors other than enhanced meat quality could be responsible for consumer preference for meat from free-range poultry.
Keywords: zvířata; Animals; chov zvířat; Chickens; Meat; Animal Husbandry; kur domácí; maso